Peran Al-Quran dan Hadist dalam Pembentukan Etika Sosial di Era Digital - Toni Gunawan Rambe; Tulus Musthofa; Nur Saidah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article discusses the importance of the Al-Quran and Hadith as the main sources of Islamic teachings in shaping social ethics in the digital era. In the context of continuously developing technology, the main challenge faced is how to integrate moral values ​​originating from the Koran and Hadith into everyday life which is increasingly influenced by digital media. The Koran provides a strong moral foundation, including respecting individual rights and maintaining justice, while the Hadith of the Prophet Muhammad SAW provides concrete examples of how to apply these teachings in social life. This article examines the relevance of these teachings in dealing with phenomena such as cyberbullying, hate speech, and other challenges in digital interactions. This research uses a descriptive qualitative approach with a focus on literature study as the main methodology. The research results show that a deep understanding of the Al-Quran and Hadith is important for developing strategies to overcome the complexity of social ethics in the digital era, which allows Muslims to maintain noble values ​​in social interactions in an increasingly connected virtual world.